Synergistic Test of Chitosan-Ozonated Olive Oil and Chitosan-Coenzyme Q10 as Bone Graft Materials - Herawati, Dahlia; Babgei, Ainun Mardiah; Anwaristi, Aprilia Yuanita; Supriatno, S (2022)
Chitosan contains two reactive groups (amino and hydroxyl), which can be chemically or physically modified, thereby chitosan has a high potential in tissue engineering applications. Chitosan is an ingredient that is often used as a graft material, however, it is less osteoconductive when not combined with other materials. Other ingredient that possess high antioxidants and can be used routinely, both topically and systemically is coenzyme Q10 in the treatment of periodontal conditions. Ozonated olive oil is also used as a therapeutic agent in inflammation to stimulate and accelerate the healing of soft tissues and bones. In the present study, the synergy of chitosanozonated olive oil combination and coenzyme Q10-chitosan gel combination on the increase of bone formation was examined. A purely laboratory experimental study was carried out in this study. Synergy measurement of chitosan combination was delivered by FTIR spectrum test and MTT assay. The results revealed that between the combination of chitosan-ozonated olive oil and chitosan-coenzyme Q10 gel had the same spectrum graph as pure chitosan. This data showed that the combination of both materials did not form a new reaction. Furthermore, the MTT assay showed that the combination of chitosan-ozonated olive oil and chitosan-coenzyme Q10 gel were not toxic and could increase the number of fibroblast cells. In conclusion, the combination of chitosanozonated olive oil and gel chitosan-coenzyme Q10 indicated a synergistic relationship without mutual influence and non-toxicity.